Encyclopedia of the world's biomes - Goldstein, Michael I.; DellaSala, Dominick A., 1956- (Elsevier Academic Press, 2020)
"Encyclopedia of the World's Biomes is a unique, five volume reference that provides a global synthesis of biomes, including the latest science. All of the book's chapters follow a common thematic order that spans biodiversity importance, principal anthropogenic stressors and trends, changing climatic conditions, and conservation strategies for maintaining biomes in an increasingly human-dominated world. This work is a one-stop shop that gives users access to up-to-date, informative articles that go deeper in content than any currently available publication"--